The school's contingent registration data cloud to keep track of student progress - V. K. Tolstykh; A. Iu. Kozhemiakin (Academy of Cognitive and Natural Sciences, 2013)
To solve the problem of collecting and maintaining up-to-date personal data on the participants of the educational process and data on the progress of students it is proposed to use a virtual database - some cloud of personal files storage for the information system of the educational institution. It should consist of a local database of the contingent of the educational institution and its achievements, as well as a remote database of some third-party organization that provides support for current personal data of all participants in the educational process, for example - a unified registration database of citizens.